2020
DOI: 10.1038/s41598-020-64067-4
|View full text |Cite
|
Sign up to set email alerts
|

Variation of 4 MV X-ray dose rate strongly impacts biological response both in vitro and in vivo

Abstract: Whereas an RBE > 1 is described for very low-energy X-ray beams (in the range of 25-50 kV), there is a consensus that the RBE of X-rays (from 0.1 to 3 MeV) is equal to 1, whatever the energy or dose rate of the beam. Comparisons of X-ray beam dose rates are scarce even though these beams are widely used in medical diagnosis or radiotherapy. By using two dose rates (0.63 and 2.5 Gy.min −1) of high-energy X-rays on normal endothelial cells (HUVECs), we have studied the clonogenic assay, but also viability/ morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…This conclusion fits well with recently reported effects of ultra-high dose rate (UHDR) on melanoma cells (Buontempo et al 2018 ). Also, the presented results support the recent multiparametric study, demonstrating a higher biological effectiveness of 4 MV photons delivered at a dose rate of 2.5 Gy min −1 as compared to 0.63 Gy min −1 (Ben Kacem et al 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…This conclusion fits well with recently reported effects of ultra-high dose rate (UHDR) on melanoma cells (Buontempo et al 2018 ). Also, the presented results support the recent multiparametric study, demonstrating a higher biological effectiveness of 4 MV photons delivered at a dose rate of 2.5 Gy min −1 as compared to 0.63 Gy min −1 (Ben Kacem et al 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…The endothelial cell model of radiation-induced dysfunction we used has been extensively characterized in our previous work ( Ben Kacem et al., 2020 ; Heinonen et al., 2015 , 2018 ; Jaillet et al., 2017 ; Paget et al., 2019 ). In this model, at a dose of 20 Gy, the cells stopped proliferating as early as one day after irradiation and did not proliferate at all by the third day ( Ben Kacem et al., 2020 ; Paget et al., 2019 ). In addition, we estimated that at day 7 post-20 Gy only 2%–3% of cells had divided, and at most once, during the first 7 days after irradiation ( Paget et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a clear distinction must be made with very low-energy X-ray beams (in the range of 25-50 k V) for ave been reported (Slonina et al, 2003;Gomolka et al, 2005). Moreover, we recently demonstrated that when using a multiparametric RBE measurement approach, the RBE of photons deviated from 1 when varying the dose rate of high-energy X-rays (Ben Kacem et al, 2020) as well as varying the X-ray energy between 220 kV and 4 MV (Paget et al, 2019).…”
Section: Introductionmentioning
confidence: 93%